2020
DOI: 10.1088/1757-899x/883/1/012074
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hydrogels on moisture storage of irrigated automorphic soils in Uzbekistan

Abstract: An experimental study on the development of water-conserving irrigation technology with the use of super swelling hydrogels synthesized out of local raw material has been conducted for three years under the condition of arid automorphic soils of western Uzbekistan. The development of new and affordable water-conserving technologies is critical for the sustainable development of irrigated agriculture in arid zones that severely affected by growing water scarcity. The experiments were aimed at determining the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Salokhiddinov, A. According to the research results of Khamidov, V. Boirov and L. Yusupov, strong swelling hydrogels used in dry farming have a significant positive effect on winter wheat [13,14,15].…”
Section: The Relevance Of the Topicmentioning
confidence: 99%
“…Salokhiddinov, A. According to the research results of Khamidov, V. Boirov and L. Yusupov, strong swelling hydrogels used in dry farming have a significant positive effect on winter wheat [13,14,15].…”
Section: The Relevance Of the Topicmentioning
confidence: 99%
“…In another study, Ramanjaneyulu et al [86] found that hydrogel application failed to enhance the seed yield of rainfed castor in alfisols due to its long duration, intermediate nature, and inherent ability to withstand short-term droughts. Salokhiddinov et al [87] noticed that the use of highly swellable polymer hydrogels under conditions of automorphic soils based on improved traditional furrow irrigation technology had made it possible to reduce water consumption for irrigation by 15-17% in the first year, by 12-14% in the second year, and by 9-11% in the third year of experiments in cotton crop. Due to the longer duration of moisture conservation in the soil, the period between irrigations was extended by 10-12 days; the number of irrigations is reduced.…”
Section: Practical Assessment Of Hydrogel In Agriculturementioning
confidence: 99%